Correlation of Molecular Rapid Test Results with Eosinophil Levels in Suspected Pulmonary Tuberculosis Patients at Ciracas Hospital - Syahidah, Zainab Durratus; Foekh, Neiny Prisy; Aisy, Dzia Ulhaq Rohadatul (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Case Detection Rate conducted to overcome pulmonary tuberculosis, which is screening of pulmonary TB cases. Molecular rapid tests are a greater method used for detecting MTB. Pulmonary TB disease can affect hematology, one of which is eosinophil levels to determine severity of infection. This study aims to determine the correlation of TCM results with eosinophil levels in patients with suspected pulmonary TB at RSUD Ciracas. This type of research is quantitative, observational, and analytic with cross sectional design. The study was conducted at RSUD Ciracas in November 2024 - May 2025 with a total sample of 47 medical records of TCM results and eosinophil levels of patients with suspected pulmonary TB from January to December 2024. Analysis was performed with the Chi-Square test to determine the correlation between variables. Based on gender, there were 31 (66%) male patients and 16 (34%) female patients, while the age category was adult (20-60 years), 35 (74.5%) patients, and elderly (>60 years), 12 (25.5%) patients. Based on TCM results with negative MTB 30 (63.8%) patients and positive MTB 17 (36.2%) patients, while the results of eosinophil levels were normal 16 (34%) patients and abnormal 31 (66%) patients.